Urgensi Desain Struktur Organisasi Terhadap Strategi Dalam Meningkatkan Kinerja Organisasi - Nabila Cesya Rahmalia; Hesti Kusumaningrum; Siti Fatikhatus Sya’adah (Al-Gafari : Manajemen dan Pendidikan, 2024)
Facing the progress of an increasingly sophisticated era, of course, the right steps are needed to dare to advance in the face of the era of the rise of organizational development, so that taking steps for the future is certainly very concerned, especially making organizational design, the urgency of making organizational design determines taking the right strategy. Through taking the right strategy in the organizational structure, the organization can facilitate the exchange of knowledge and communication between members and uphold the moral standards and performance of employees to be more professional. This research uses a literature study methodology, retrieving this data source through analysis of various literature sources. The results of this discussion provide an understanding that strategies are assembled to organize and implement strategies to achieve various predetermined goals while maintaining and expanding organizational activities. With an organizational structure that is flexible and in line with current developments, organizations can more easily adapt and move quickly to anticipate changes. After going through this research, it can be seen that there is an urgency from the existence of an organizational structure to its strategy in the organization. The organizational structure also determines the arrangement of interaction patterns and leads to the achievement of the performance set by the organization. Therefore, organizations must continue to develop and update their organizational structure to remain relevant and effective in achieving their goals.